Identification of host plant use of adults of a long-distance migratory insect, Mythimna separata. - Yongqiang Liu; Xiaowei Fu; Limi Mao; Zhenlong Xing; Kongming Wu (PLoS ONE)
Adults of many insect species often become contaminated with pollen grains when feeding. Identification of plant hosts for M. separata moths could increase our understanding of their geographic origin and the coevolution of M. separata moths and their host plants. However, identifying the diet of noctuid moths using traditional direct observation is limited by their nocturnal and flight habits. In this study, we used core barcode markers and pollen morphology to identify pollen species. We found pollen from 13 plant species belonging to nine families on trapped M. separata moths, mainly from Angiosperm, Dicotyledoneae. Pollen was found on 14.4% and 12.3% of females and males, respectively, and the amount of pollen transported varied with the body part, with the most pollen on the proboscis. We were able to determine from this that the moths visited woody plants more than herbaceous plants, but not significantly so, and that they carried more pollen earlier in the migration season. In this study, we clarified the species and frequencies of pollen deposition on M. separata moths. These findings improve our understanding of the coevolution of the moths and their host plants. Identification of plant hosts for adult moths provides a new means of studying noctuid moth-host plant interactions, and informs the development of more efficient management practices for M. separata.